Future directions of Doctor of Public Health education in the United States: a qualitative study - Park, Chulwoo; Migliaccio, Gene; Edberg, Mark; Frehywot, Seble; Johnson, Geralyn (BMC public health, 2021)
Background The Doctor of Public Health (DrPH) degree is an advanced and terminal professional degree that prepares the future workforce to engage in public health research, teaching, practice, and leadership. The purpose of the present research was to discuss the desirable future direction and optimal education strategies for the DrPH degree in the United States. Methods A total of 28 Council on Education for Public Health (CEPH)-accredited DrPH programs in the United States was identified through the Association of Schools and Programs of Public Health (ASPPH) Academic Program Finder. Then, a qualitative analysis was conducted to obtain perspectives from a total of 20 DrPH program directors through in-depth interviews. Results A DrPH program should be recognized as equal but different from an MPH or a PhD program and strengthen the curriculum of methodology and leadership education. It is important that a DrPH program establishes specific partnerships with other entities and provide funding for students. In addition, rather than being standardized nationwide, there is value in each DrPH program maintaining its unique character and enabling students to be open to all career pathways. Conclusions The future of DrPH programs in the twenty-first century should aim at effective interdisciplinary public health approaches that draw from the best of both academic and applied sectors. A DrPH program is expected to provide academic, applied public health, and leadership training for students to pursue careers in either academia or the public/private sector, because public health is an applied social science that bridges the gap between research and practice.